PRIORITY OF ENSURING COMMUNITY UNITY IN STRENGTHENING STATE ADMINISTRATION - Asatov Akmal Ismatovich (American Journals Publishing, 2024)
The article analyzes community solidarity as a pillar of the modern social state. The state, in the performance of its social, economic internal and external functions, necessarily relies on a normal and stable society. In this way, if the society is socially united, all residents will be equally interested in the reforms in this regard. Also, community solidarity mitigates conflicts between different social groups and increases the efficiency of state administration. Based on its social character, the society ensures the activity of people, staying true to its traditions. The criteria for the formation of a highly moral civil society are revealed in the work.
Keywords: Society, state, government, social state, democracy, solidarity, citizenship, solidarity, harmony, harmony.